PENGARUH FOOTBALL AUSTRALIA PERFORM SELAMA ENAM MINGGU TERHADAP FLEKSIBILITAS DAN KELINCAHAN PEMAIN SEPAK BOLA REMAJA - Heri Purnama Pribadi; Dita Angelia Damayanti; Nadia Eka Yulianita Rahmasari; Ahmad Abdullah (JPK : Jurnal Penelitian Kesehatan, 2026)
Flexibility and agility are important for soccer performance and injury prevention, especially among young players. Football Australia Perform+, an updated version of the FIFA 11+ injury prevention program, has demonstrated benefits to neuromuscular control and general physical performance. However, there is limited evidence regarding its impact on flexibility and agility in adolescents. This study aimed to investigate the effect of six weeks of Football Australia Perform+ training on leg muscle flexibility and agility in adolescent male soccer players. A pre-experimental one-group pretest–posttest design was employed involving 15 male soccer players (mean ± SD: age = 17.07 ± 0.59 years; height = 169.53 ± 2.45 cm; body mass = 56.53 ± 6.29 kg). Participants completed the Perform+ program three times per week for six weeks, in addition to their regular team training. Flexibility was measured using the Y-Balance Test (YBT) in anterior, posterolateral, and posteromedial directions, while agility was assessed using the Agility T-Test. Data were analyzed using a paired-sample t-test with a significance level set at p < 0.05. Significant improvements were found in most flexibility parameters—left anterior (LA), right anterior (RA), left posteromedial (LPM), right posteromedial (RPM), and left posterolateral (LPL)—as well as in agility performance (p < 0.05). No significant difference was observed in right posterolateral (RPL) flexibility (p > 0.05). The Perform+ program effectively enhanced flexibility and agility, indicating positive neuromuscular adaptations following six weeks of training. The Football Australia Perform+ program significantly improves leg muscle flexibility and agility in adolescent soccer players, supporting its dual role in performance enhancement and injury prevention. These findings suggest that incorporating Perform+ into regular training routines can optimize physical readiness and reduce the risk of lower-limb injuries. Future studies using randomized controlled designs are recommended to further confirm these outcomes and explore long-term performance effects.